1991
DOI: 10.1002/jmv.1890350313
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of in vitro anti‐HBs producing B cells (spot‐ELISA) following primary and supplementary vaccination with a recombinant hepatitis B vaccine in insulin dependent diabetic patients and matched controls

Abstract: A prospective study of the immune response after hepatitis B vaccination was carried out in 32 insulin dependent diabetes mellitus (IDDM) patients and their age and sex matched healthy controls. A sensitive, immunoenzymatic technique was used, able to detect in vitro specific antibody production by mitogen stimulated individual B cells. In-vivo serologic response after vaccination with a standard scheme (0, 1 and 6 months) of 20 micrograms recombinant hepatitis B (HB) vaccine was significantly impaired in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 29 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…We observed positive lymphocyte proliferative responses in 7 of the 12 subjects, although the maximal proliferation was lower than that in vaccine recipients with positive serum antiHBs. We previously reported that an immunological B cell memory to hepatitis B after a vaccination existed in healthcare personnel though serum anti-HBs titers were decreased with time or not measurable in some cases [32] . The long term efficacy of hepatitis B vaccination was also investigated in China and it was found that the protective efficacy of hepatitis B vaccination was still existed with a low risk of becoming a carrier and a low serum level of neutralizing antibody even at the time of 12 years after vaccination [9] .…”
Section: Discussionmentioning
confidence: 99%
“…We observed positive lymphocyte proliferative responses in 7 of the 12 subjects, although the maximal proliferation was lower than that in vaccine recipients with positive serum antiHBs. We previously reported that an immunological B cell memory to hepatitis B after a vaccination existed in healthcare personnel though serum anti-HBs titers were decreased with time or not measurable in some cases [32] . The long term efficacy of hepatitis B vaccination was also investigated in China and it was found that the protective efficacy of hepatitis B vaccination was still existed with a low risk of becoming a carrier and a low serum level of neutralizing antibody even at the time of 12 years after vaccination [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis, malignant external otitis, emphysematous pyelonephritis and emphysematous cholecystitis diseases are known to be strongly associated with diabetes [11]. On the other hand, in the studies on hepatitis immunology in patients with DM, it was found that diabetic patients generated a significantly lower antibody response compared to healthy subjects [1416]. While the frequency of HCV infection worldwide is around 3%, the frequency of HBV infection varies between 0.1% and 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to detect and validate HBsAg-specific T-and B-cell reactivity in vaccinees to show the presence of T-and B-cell memory (9,18,26,27). The results, however, were contradictory, probably due to the different detection systems used and the limited sensitivity of some of the methods applied.…”
Section: Introductionmentioning
confidence: 99%